2007
DOI: 10.1124/jpet.107.127407
|View full text |Cite
|
Sign up to set email alerts
|

Acetylbritannilactone Inhibits Neointimal Hyperplasia after Balloon Injury of Rat Artery by Suppressing Nuclear Factor-κB Activation

Abstract: Based on our previous observations that 1-O-acetylbritannilactone (R)-4((3aS,4S,7aR)-4-hydroxy-6-methyl-3-methylene-2-oxo-2,3,3a,4,7,7a-hexahydrobenzofuran-5-yl)pentyl acetate (ABL) suppresses prostaglandin E 2 and nitric oxide synthesis in macrophages, the present study was designed to explore the effect of ABL on neointimal hyperplasia after balloon injury and its mechanism of action. In male Sprague-Dawley rats, 26 mg/kg ABL or polyglycol (control) was administered daily from 3 days before injury to 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…We found that ABL markedly inhibited the NF-κB and TLR4 expression induced by MCAO and OGD and increased the expression of MyD88, SOCS1 and I-κB. This is consistent with previous findings that ABL could suppress NF-κB activation and block the binding of active NF-κB to the target gene promoters (19)(20)(21). Our results suggest that ABL exerts its inhibitory effect on the ischemia-induced inflammation via abrogating the ischemia-induced upregulation of NF-κB and TLR4 and inducing the expression of MyD88, SOCS1 and I-κB.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that ABL markedly inhibited the NF-κB and TLR4 expression induced by MCAO and OGD and increased the expression of MyD88, SOCS1 and I-κB. This is consistent with previous findings that ABL could suppress NF-κB activation and block the binding of active NF-κB to the target gene promoters (19)(20)(21). Our results suggest that ABL exerts its inhibitory effect on the ischemia-induced inflammation via abrogating the ischemia-induced upregulation of NF-κB and TLR4 and inducing the expression of MyD88, SOCS1 and I-κB.…”
Section: Discussionsupporting
confidence: 82%
“…Its chemical structure is different from ergolide, which was isolated previously (18). Several of the previous studies demonstrate that ABL inhibits the expression of inflammation-associated genes, such as the NOS and COX-2 genes, by reducing IκB-α phosphorylation and degradation, inhibiting NF-κB activation and blocking the binding of active NF-κB to the target gene promoters in RAW 264.7 macrophages and vascular smooth muscle cells (VSMCs) (19)(20)(21). In addition, ABL also can suppress PDGF-induced DNA synthesis and cell proliferation, subsequently leading to apoptosis in proliferative VSMCs via the induction of a higher ratio of Bax/Bcl-2, activation of caspase-9/-3 and the cleavage of the endogenous substrate Poly (ADP-ribose) polymerase (22).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although the effect of PGE 2 on VSMC proliferation has been reported by several groups, the results are inconsistent, with both inhibitory and stimulatory effects reported. [17][18]47,48 PGE 2 exerts its biological roles by 4 EP receptors, EP1 to EP4. Activation of EP receptors, with characteristic vascular distribution, evokes receptor-specific signaling pathways and results in distinct biological consequences.…”
mentioning
confidence: 99%
“…Several proteins regulated by KLF4 such as p21, cyclin E are also targeted by ABL (4,24). Thus, we hypothesized that ABL may reduce proliferation by promoting the KLF4 activity.…”
Section: Abl Induces Klf4 Expression In Ht-29 Cellsmentioning
confidence: 99%
“…1) and has been shown to possess anti-inflammatory and anticancer activities (4)(5)(6)(7)(8). Moreover, ABL has been shown to inhibit the expression of cyclooxygenase-2 (COX-2) that plays a significant role in colon carcinogenesis (9,10).…”
Section: Introductionmentioning
confidence: 99%